Sistem Informasi Dengan Pendekatan Customer Relationship Management (CRM) Menggunakan Metode Service Quality - Diah Tri Wahyuni; Tacbir Hendro Pudjiantoro; Asep Id Hadiana (Jurnal ICT : Information Communication & Technology, 2020)
Anna Salon Spa is a beauty care business or service that provides various kinds of treatments. Primary data were obtained from interviews with Anna salon spa employees, while secondary data used library sources and research results and data collection techniques used interview, observation and documentation techniques. In this study, problems were found such as the difficulty in determining customer loyalty, the difficulty in calculating the cost optimally, the difficulty in conducting transaction recapitulation because there may be data missing or not being calculated correctly because Anna Salon Spa is still recording the data in the ledger. In addition, another problem that arises is the delivery of promotions that take more time because they have to send the same message one by one to customers or via Instagram and Facebook. The method uses the calculation of the actual value of service quality by comparing the value of customer perceptions with the value of customer expectations and expressed in percent, this method aims to determine the extent of service performance and measure customer satisfaction. To solve this problem is to build an information system with a web-based customer relationship management (CRM) approach that provides input to the applications used by Anna Salons Spas so as to provide comfort and satisfaction for customers and can help provide better, timely information systems. , and is accurate and recommends the right service so that it benefits the company. The use of service quality methods in this study is to know the value and measure customer satisfaction through the questionnaire given to customers.